A dictionary of media and communication / Daniel Chandler, Rod Munday - Chandler, Daniel
"This authoritative and up-to-date A-Z covers all aspects of interpersonal, mass, and networked communication in over 3500 entries, including digital and mobile media, advertising, journalism, social media, and nonverbal communication."-